The internalization of school environmental care through Adiwiyata program - Saadah, Lailatus; Rusnaini, Rusnaini; Muchtarom, Moh (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
Low levels of education impact a lack of understanding of the environment importance. One serious effort to increase awareness of environmental protection and management is through the world of education, both formal and non-formal education. Schools become a forum for conducting environmental education through holding environmentally friendly schools. This research aims to analyze the internalization of environmental care in schools through the Adiwiyata program. This research uses a qualitative approach. The location of the study was at Junior High School 1 Panawangan Grobogan. Researchers collected data through observation, interviews, and documentation methods. Interviews were conducted with the civic education teacher, six students, the school principal, and the chief coordinator of the Adiwiyata program. Data reduction, data presentation, and conclusion drawing were carried out by researchers as data analysis techniques. This research shows that internalizing environmental care can be done by implementing the components of the Adiwiyata program at Junior High School 1 Panawangan. Apart from that, the program is also supported by strengthening civic disposition given to Civics subjects. The Adiwiyata program combines learning and action that effectively changes student behavior to be more participatory in protecting the environment. This research has implications for schools to be able to collaborate with external parties such as environmental agencies, NGOs and environmental communities to increase students' understanding of current ecological issues. This collaboration can involve outreach activities, field trips, and environmental projects that actively involve students.